2010
DOI: 10.1111/j.1467-8659.2010.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

Free Path Sampling in High Resolution Inhomogeneous Participating Media

Abstract: This paper presents efficient algorithms for free path sampling in heterogeneous participating media defined either by high-resolution voxel arrays or generated procedurally. The method is based on the concept of mixing 'virtual' material or particles to the medium, augmenting the extinction coefficient to a function for which the free path can be sampled in a straightforward way. The virtual material is selected such that it modifies the volume density but does not alter the radiance. We define the total exti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 18 publications
0
45
0
Order By: Relevance
“…constant control extinction in our case) can reduce variance if it decreases the rate of change of the residual exponentiated integral. The residual tracking is also related to the "separation of main part" applied by Szirmay-Kalos et al [2011] to the evaluation of optical thickness. However, their approach will be effective only if the main part is represented by a non-constant function that matches the extinction function well.…”
Section: Residual Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…constant control extinction in our case) can reduce variance if it decreases the rate of change of the residual exponentiated integral. The residual tracking is also related to the "separation of main part" applied by Szirmay-Kalos et al [2011] to the evaluation of optical thickness. However, their approach will be effective only if the main part is represented by a non-constant function that matches the extinction function well.…”
Section: Residual Trackingmentioning
confidence: 99%
“…Unbiased free-flight sampling routines can also be used for estimating transmittance [Raab et al 2008;Szirmay-Kalos et al 2011;Jarosz et al 2011]: if the sampled free flight distance is greater than d, the transmittance is estimated as 1, and 0 otherwise. The binary estimate can be further refined by averaging multiple instances, i.e.…”
Section: Free-flight Sampling As a Transmittance Estimatementioning
confidence: 99%
“…To improve efficiency, the original medium is usually approximated by functions allowing analytical integration and sampling. Note that recently, sampling of arbitrary media has received a lot of attention [14,15]. An accurate and multi-resolution representation is the octree.…”
Section: Discussionmentioning
confidence: 99%
“…Woodcock tracking is a technique developed in the particle physics field for unbiased mean-free path sampling. Several recent graphics techniques [Raab et al 2008;Szirmay-Kalos et al 2011] have employed this, in combination with Equation (20), for estimating transmittance in heterogeneous media.…”
Section: Evaluating γ In Heterogeneous Mediamentioning
confidence: 98%
“…We found that performance loss of each pass is primarily due to multiple evaluations of Perlin noise, which is quite expensive both on the GPU and CPU. Accelerated variants of Woodcock tracking [Yue et al 2010;Szirmay-Kalos et al 2011] could help to reduce the number of density evaluations needed for free-path sampling.…”
Section: Limitations and Future Workmentioning
confidence: 99%